The mediating effect of employee commitment on recruitment process towards organizational performance in UAE organization - Ali Alansaari, Omar Ibrahim; Md Yusoff, Rosman; Ismail, Fadillah (Growing Science, Canada, 2018)
The primary objective of this paper is to investigate the impact of the recruitment process on the organizational performance. It has been hypothesized in this study that an effective recruitment process could enhance the organizational process. After critically reviewing the literature, the study finds employee commitment as a key factor which affects the relationship between recruitment process and organizational performance. Therefore the second objective of the current study is to investigate the mediating role of employee commitment in the relationship between recruitment process and organizational performance. The data is collected from 247 employees of Fujairah National Group of UAE and the structural equation modeling using AMOS is used to analyze the data. The findings of the study show a great deal of agreement with the results. The findings of the study will be helpful for HR practitioners, policymakers and researchers in understanding the relationship between employee commitment, recruitment process, and organizational performance.